Analysis of Changes in Student Activity and Learning Patterns During the Pandemic: Case Study of High School Students in Jember Regency - Noviyanti Noviyanti; Firdatul Magfiroh; Alip Nur Wahyudi; Rully Putri Nirmala Puji (Pancaran Pendidikan, 2020)
The Covid-19 pandemic had a significant impact on education. This is indicated by the introduction of an online learning system. Changes in the learning system either directly or indirectly will affect student learning activities and patterns. The purpose of this study is to identify differences in student activities and learning patterns during the pandemic. This research uses a mix of comparative and qualitative quantitative methods. Quantitative data collection is done by using an online questionnaire via Google Form, while qualitative data is collected through a questionnaire in the description and literature. This study involved 100 student respondents in high schools in Jember. Data analysis using IBM SPPS Wilcoxon different tests. The results of data analysis showed there were differences in activities and learning patterns experienced by students before and during the pandemic. Student activity and learning patterns tend to decrease during the pandemic. The learning process constraints faced by students during this pandemic are connections, assignment methods (assignments tend to be many), delivery methods, and poor time management